Sociological Orientation of Islamic Education Perspective of the Quran - Ahmad Suhaemi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2017)
Islamic education as part of the national education system has a purpose want to achieve. In the process, Islamic education is inseparable from the problems faced. In the current postmodern era, Islamic education should be used as a forum the seedbed of tolerance to maintain harmony and peace. The Quran and Hadith as the main source of Islamic education must be reinterpreted and integrated with other approaches. One approach that can be integrated is with internalize socio-cultural values in learning. This approach offers a synthesis to deal with the seeds of intolerance that have begun to grow deep this nation's young generation. It is hoped that internalization of these values will be created social harmony that can be used as provisions by young Muslims in life sociable.